Proses Keagenan dalam Perpanjangan Sertifikat Safe Manning di Kantor Syahbandar Kelas IV oleh PT. Bahtera Adhiguna Cabang Pangkalan Susu: Penelitian - Meriah Kita Deliani; L. Samuel Simangunsong (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The agency process in managing the Safe Manning Certificate constitutes a crucial function of shipping agents acting on behalf of ship owners or operators to ensure legal and safe vessel operations. The Safe Manning Certificate is a mandatory document specifying the number and qualifications of crew members required to maintain maritime safety, security, navigation, port operations, and marine environmental protection. This study aims to analyze the role of shipping agencies in the renewal process of the Safe Manning Certificate and to identify challenges encountered during its implementation. The research was conducted at PT Bahtera Adhiguna, a shipping company actively coordinating with the Harbourmaster and Port Authority Office (KSOP) of Pangkalan Susu and other relevant institutions. The research employed field research methods through observation and interviews, complemented by library research by reviewing relevant regulations and academic literature. The findings indicate that PT Bahtera Adhiguna plays a significant role in document preparation, administrative coordination, and communication facilitation between the vessel and the KSOP. However, several challenges were identified, including delays in submitting initial documents by the vessel, limited awareness among some crew members regarding the importance of the Safe Manning Certificate, and human resource constraints at the KSOP of Pangkalan Susu.